Physiological and molecular mechanisms of drought adaptation in foxtail millet: insights and future perspectives - Gao, Hui; Liu, Jiaxin; Li, Shen; Zou, Luming; Wang, Yulu; Li, Lin; Zhang, Ting; Zhao, Ling; Wang, Genping; Zhang, Haoshan (Frontiers in Plant Science, 2025)
Drought stress poses a major challenge to global agriculture under accelerating climate change. Foxtail millet (Setaria italica), a C4 crop native to China, has emerged as both a coarse grain crop in arid regions and a model for studying drought adaptation. This mini review synthesizes recent advances in understanding the multi‐level drought response network of foxtail millet, encompassing root system remodeling, stomatal regulation, osmotic adjustment, and photosynthetic and metabolic reprogramming. These physiological processes are coordinated by interconnected signaling modules involving Ca²+, reactive oxygen species (ROS), and abscisic acid (ABA), and are transcriptionally fine‐tuned by transcription factors (TFs), non‐coding RNAs, and epigenetic modifications. We also emphasize the genetic and germplasm diversity underlying drought tolerance, highlighting foxtail millet’s potential as a comparative C4 model for functional genomics and climate‐resilient breeding. Despite substantial progress, critical gaps remain in understanding hormone crosstalk, root–shoot signaling, and the integration of metabolic and transcriptional responses. Future research integrating pan‐genomics, multi‐omics, and precision genome editing, combined with translational breeding aimed at enhancing yield stability under climate variability, will deepen mechanistic understanding and accelerate the improvement of drought‐resilient cereal crops.